If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -15 = 30 + 2x Reorder the terms: -15 + 5x = 30 + 2x Solving -15 + 5x = 30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 5x + -2x = 30 + 2x + -2x Combine like terms: 5x + -2x = 3x -15 + 3x = 30 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 3x = 30 + 0 -15 + 3x = 30 Add '15' to each side of the equation. -15 + 15 + 3x = 30 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 30 + 15 3x = 30 + 15 Combine like terms: 30 + 15 = 45 3x = 45 Divide each side by '3'. x = 15 Simplifying x = 15
| 7x-4(2x-9)=50 | | (1/2x)-4=3-(1/3x) | | 23-2x=22 | | 9f+6g-4f-2g+2= | | 16x^2+8x+2=10 | | 5(x+6)=3(x-5) | | 3y+6=-18 | | -0.375h=-12 | | 36x+159= | | 5x-15=30+2 | | 2x+1y=78 | | -2.6h=-12 | | 8(x+4)=6(x-2) | | (5x+4)(3x+2)=(7x-1)(3x-5)+60x-51 | | 2(5+w)=94-w | | 1=7-3x | | 7p=7(4p+9) | | (5+2w)+w=94 | | x=(-8) | | 5m-2m+4m-6m= | | 4.7x-39=2.3x+9 | | 6(6x+6)=36x+36 | | 6ab-3ba= | | 5x^2-36x-108=0 | | 14k-70=42 | | 4x^2-10x-288=x^2-22x | | 2(x)+x=180-63 | | 2k-10=-42 | | x+(3x-10)=90 | | (7*3)-n=9 | | 9/5•42 | | Logb(6x^4)-7logb(x)=0 |